2022
DOI: 10.30643/jiksht.v17i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Gaya Hidup Sedentary Terhadap Kejadian Tinggi Prediabetes di Wilayah Kerja Puskesmas Johar Baru

Abstract: Introduction: The incidence of prediabetes risk increases every year. This can occur as a result of  lack on physical activity which is exacerbated by a pandemic condition that strengths people to stay at home more. Objectives:  This study was conducted to determine the relationship between a sedentary lifestyle towards the incidence of prediabetes in the working area of the Johar Baru Health Center. Methods:  The study design used is descriptive correlation with a cross sectional approach. The sample in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…The type of individual work that sits in front of a computer screen for 6-8 hours every day has an irregular eating and sleeping schedule, triggers a hormonal imbalance that regulates the balance of eating and energy expenditure so that this triggers an increase in risk factors for prediabetes (Arania et al, 2021). This is in line with research conducted by (Dwi & Ambarita, 2022), that many respondents have a sedentary activity sedentary lifestyle and the incidence of prediabetes p-value 0.027.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The type of individual work that sits in front of a computer screen for 6-8 hours every day has an irregular eating and sleeping schedule, triggers a hormonal imbalance that regulates the balance of eating and energy expenditure so that this triggers an increase in risk factors for prediabetes (Arania et al, 2021). This is in line with research conducted by (Dwi & Ambarita, 2022), that many respondents have a sedentary activity sedentary lifestyle and the incidence of prediabetes p-value 0.027.…”
Section: Resultssupporting
confidence: 73%
“…Another Research from (Dwi & Ambarita, 2022) found that a sedentary lifestyle will increase the risk of prediabetes. Physical activity helps regulate blood sugar levels, because the glucose stored in the muscles will be converted into energy when doing activities that trigger muscle contractions.…”
Section: Resultsmentioning
confidence: 99%
“…Sebagian besar para pekerja mengalami sindrom metabolik yang salah satunya adalah hiperglikemia dimana kadar glukosa darah puasa lebih dari 100 mg/dL sebanyak 47 pekerja (71,2%) (Yusfita et al, 2018). Penelitian lainnya juga mendapatkan hasil yang serupa yaitu terdapat hubungan yang bermakna antara gaya hidup sedentari dengan prediabetes di Puskesmas Johar Baru (p=0,027) (Ambarita et al, 2022). Prediabetes merupakan keadaan dimana kadar gula darah puasa seseorang berkisar antara 100 -125 mg/dL.…”
Section: Pembahasanunclassified
“…Saat kontraksi otot berkurang maka dapat menghambat proses diubahnya gula dalam otot menjadi energi sehingga mempengaruhi penurunan kadar gula darah. Hal ini menyebabkan penurunan efektivitas insulin dan buruknya penggunaan glukosa dan lemak di dalam sel (Ambarita et al, 2022). Kurang aktivitas fisik menyebabkan gangguan pada insulin sehingga terjadi hiperglikemia.…”
Section: Pembahasanunclassified